Perbedaan Perubahan Tekanan Darah Antara yang Diberikan Jus Mentimun (Cucumis Sativus Linn) dengan Jus Pepaya (Carica Papaya) Terhadap Penderita Hipertensi Primer di Wilayah Kerja Puskesmas Ampenan - Rahman, Taufiqur (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Hypertension is the leading cause of death in Indonesia and has a high risk of heart failure, stroke, kidney failure and myocardial infarction. Management of hypertension includes lifestyle changes, diet, stress management and others. In addition, giving cucumber juice and papaya juice is also recommended as a nursing management to lower blood pressure because the content of potassium, magnesium, phosphorus can treat hypertension. The purpose of this study was to determine the difference in blood pressure changes between those given cucumber juice (cucumis sativus linn) and papaya juice (carica papaya) for patients with primary hypertension in the Ampenan Health Center work area. The research method used was a Quasy Experimental study with a pretest-posttest control group design with a quantitative approach in the cucumber juice group and the papaya juice group with a control group without treatment. Random sampling technique was used to obtain 30 respondents divided into 3 groups. The results of the study showed that the results of the dependent t test showed a p value = <0.05 so that there was a difference in blood pressure reduction between those given cucumber juice and those given papaya juice in patients with hypertension.